CRISPR-Cas12a-driven MXene-PEDOT:PSS piezoresistive wireless biosensor. (April 2021) - Zeng, Ruijin; Wang, Weijun; Chen, Mingming; Wan, Qing; Wang, Caicheng; Knopp, Dietmar; Tang, Dianping
Abstract: Beyond extraordinary in vivo accurate gene editing and regulation capabilities, the CRISPR-Cas-associated biotechnology has created a new era of in vitro nucleic acid sensing due to its inherent high-efficiency enzyme cleavage activity and robustness. However, most of the existing CRISPR-Cas systems are largely involve fluorescent reporters or lateral flow strips biosensor and can't fully explore their potential applications (sensitivity and field-deployable) due to the lack of effective signal transduction and wireless data transmission with smartphone readout. Herein, a CRISPR-Cas12a-mediated instrument-free based on ﬂexible interdigitated electrodes-modified piezoresistive block [abrasive paper-molded microstructure polydimethylsiloxane (PDMS) and MXene (Ti3 C2 Tx )-PEDOT:PSS film] was designed for point-of-care of human papillomavirus (HPV)-related DNA with integrated-module smartphone visual readout. Biotin/thiol-modification single-stranded DNA (ssDNA), acts as a linker between Au@Pt nanoparticles (Au@PtNPs) and streptavidin-coated magnetic bead (MB), are non-specifically cleaved by Cas12a when the guide RNA binds to the target HPV-DNA. Released and separated Au@PtNPs efficiently catalyzes H2 O2 to O2, and further compress the Ti3 C2 Tx -PEDOT:PSS/PDMS in a 3D-printed home-made pressure-tight vessel, thus causing the increasing current of the whole circuit thanks to contacting deformation of Ti3 C2 Tx -PEDOT:PSS/PDMS module and interdigital electrode. After integrating the Bluetooth device and wireless sensing technology in the circuit, the current signal of the target DNA can be wirelessly collected and recorded in real-time and further transmitted/displayed to the mobile terminal of the smartphone. This all-in-one detection mode not only bridges the technological gap between biological signal conduction, wireless transmission, and smartphone interface but also improves the portability and the sensitivity (more than one order of magnitude lower than that of traditional CRISPR-Cas12a biosensors). We expect that a powerful CRISPR-Cas12a system coupled with piezoresistive sensor with wireless transmission technology will become a great demonstration and widely used in real-time wireless biomedical analysis, portable point-of-care health monitoring, and molecular diagnostics. Graphical Abstract: ga1 Highlights: Combining CRISPR Cas12a-based gas reaction with wireless sensor to detect nucleic acid. Using CRISPR-Cas12a-based mode to obtain high signal transduction capabilities. The spinous microstructure can effectively respond to external stimuli.